Obesity paradox in chronic heart failure with moderately reduced or preserved left ventricular ejection fraction: impact on a prognosis for patients according to a five-year follow-up - P. P. Bidzilya; V. H. Kadzharian; M. V. Bychko (Zaporožskij Medicinskij Žurnal)
Aim. To investigate the obesity paradox by studying the impact of overweight and abdominal obesity on the prognosis in chronic heart failure (CHF) patients with moderately reduced or preserved left ventricular ejection fraction (LVEF) by five-year follow-up results.